Paralympic Science in the Genomic and Post-Genomic Era: A Historical and Critical Literature Review - Puce, Luca; Khoramipour, Kayvan; Bragazzi, Nicola Luigi (Health Nexus, 2025)
Exercise physiology has evolved from exercise biochemistry to sports and exercise genetics and, more recently, to network physiology and complex systems science of exercise: if the former was mostly reductionist, by incorporating cellular and molecular aspects, the latter leverages an integrative approach. Even though exercise physiology has been able to provide impressive insights into the genomic and post-genomic landscape that shapes the human response and adaptation to exercise and training, it has studied mostly able-bodied subjects, failing to include diverse, heterogeneous athletic populations. Only by diversifying athlete cohorts and testing them is it possible to better understand the profound interrelations and interconnections of health status, susceptibility towards injuries and diseases, underlying diseases/impairments, exercise physiology, response and adaptation to exercise, performance traits, and performance-related outcomes. Only by fully embracing pluralism and combining precision with equity, diversity, and inclusion, the “challenge of genomics” for people living with disabilities can be properly addressed and the “historic trauma” between (post-)genomic science and disability can be effectively solved and reconciled, providing the outlook necessary to decipher the molecular foundation of physical performance. In the present review, we will explore the historical evolution of sports genetics/genomics and post-genomics, utilizing a critical approach. More specifically, we will adopt a “critical disability perspective”, according to which disability is conceived as a series of lived, meaningful experiences of people with disabilities, and as social and political constructs and interpretations.